2001
DOI: 10.1002/ana.10048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical correlation in five Indian families with spinocerebellar ataxia 12

Abstract: Spinocerebellar ataxia 12 (SCA12) is a recently identified form of autosomal dominant cerebellar ataxia associated with the expansion of an unstable CAG repeat in the 5' untranslated region of the gene PPP2R2B. We analyzed 77 Indian families with autosomal dominant cerebellar ataxia phenotype and confirmed the diagnosis of SCA12 in 5 families, which included a total of 6 patients and 21 family members. The sizes of the expanded alleles ranged from 55 to 69 CAG repeats, and the sizes of the normal alleles range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 20 publications
4
76
1
Order By: Relevance
“…The repeat length ranged from 8-23 triplets in normal individuals. Anticipation, which was not detected in previous analyses (Fujigasaki et al 2001;O'Hearn et al 2001;Srivastava et al 2001;Holmes et al 2003), was also not observed in this larger study. The age at onset of the disease ranged from 26 to 56 years (mean 40.2 years) and the duration of illness at the time of examination varied from 1 to 22 years.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations
“…The repeat length ranged from 8-23 triplets in normal individuals. Anticipation, which was not detected in previous analyses (Fujigasaki et al 2001;O'Hearn et al 2001;Srivastava et al 2001;Holmes et al 2003), was also not observed in this larger study. The age at onset of the disease ranged from 26 to 56 years (mean 40.2 years) and the duration of illness at the time of examination varied from 1 to 22 years.…”
Section: Resultscontrasting
confidence: 79%
“…The 20 Indian families also included 5 families we reported in an earlier study (Srivastava et al 2001). As two unrelated affected individuals were present in one of the families (AT164), the Indian dataset included 21 unrelated expanded chromosomes.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, apart from the studies carried out in West Bengal, which reported the relative frequency of SCA3/MJD of approximately 36%, 24 the reported relative frequency of SCA3/MJD ranged from 0 to about 14% in most studies in Indian populations. 19,20,21,23 The West Bengal study is in fact an interesting exception, as earlier studies have shown a genetic relationship between the population in this area and the Tibeto-Burman speakers from Southeast and East Asia. [26][27][28][29] Also, interestingly, in Singaporeans who a are mixture of ethnic Chinese, Malays and Indians, the relative frequency of SCA3/MJD was even lower than that in ours, at about 13%.…”
Section: Discussionmentioning
confidence: 87%